The Condensed Treasure: Forgotten Impressive Video. ‘How can we Harness the Power of Social Media to Fight Poverty?’ (Global Journal of Human-Social Science, 2023)
Time is ticking seven years are remain the door of the Sustainable Development Goals SDGs closes on 2030 after the success of the Millennium Development Goals MDGs which were introduced in 2000 which focused on eight goals Eradicate Extreme Poverty and Hunger Achieve Universal Primary Education Promote Gender Equality and Empower Women Reduce child mortality and Improve Maternal Health Combat HIV AIDS Malaria and other diseases Ensure Environmental Sustainability and Develop a Global Partnership for Development and end 2015 after which the Sustainable Development Goal SDGs will replace the MDGs initiatives whose aim is to go further and end all forms of poverty The new goals are unique therefore call for action from all countries poor rich and middle-income to promote prosperity and to protect the planet